Electric field assisted cluster formation - Srivatsan Ramasubramanian. (2013)
Manipulation of colloidal particles can be extremely useful in various applications like Lab on a Chip, assembling photonic crystals, pattern replication etc. Assembling these particles into crystals by self-assembly is unique because of the bottom-up approach it provides for nanostructure fabrication compared to traditional methods of lithography.There are various ways of control particles when they self-assemble and of this electric field is a good option as it is simple, versatile and flexible. Several forces act on a colloidal particle under an electric field. Dielectrophoresis and dipole-dipole interactions act on the particles directly, while forces like electrophoresis, Electrothermal, Induced Charge Electro Osmosis and Electrohydrodynamic forces act on the particle through the surrounding fluid. V arious experimental setups have already been studied to form colloidal crystals using Dielectrophoresis as the driving force (Orlin D.Velev & Ketan H.Bhatt, 2006). However, most of these methods are in three dimensions and involve applying non-uniform electric fields to colloidal particles, which gives less control over the particle assembly. Two dimensional colloidal aggregations on electrode surface have been studied, which would give more control over the onset of particle nucleation (Ristenpart, Aksay, & D.A.Saville, 2003) (Gong, Wu, & W.M.Marr, 2002).This work, adds a new paradigm to this area by studying the effect of gold on the formation of two dimensional clusters by polystyrene particles. Addition of gold nanoparticles to polystyrene seems to increase the average displacement of particles over all the studied frequencies by almost 80%. Polystyrene particles form complex two dimensional clusters at a frequency lesser than 5 kHz while the solution with polystyrene and gold forms clusters of size less than five particles. Even though the addition of gold nanoparticles to polystyrene increases the particle displacement immensely, they still don’t form large clusters. Several possible reasons could include field distortion by gold nanoparticles and dipolar interaction between gold and polystyrene. This method can be used to fabricate small clusters in the shape of a square, triangle or wires